Effect of process parameters on microstructural and mechanical properties of friction stir welded dissimilar aluminium alloys AA 6061 and AA 7075. (9th January 2020) - Manikandan, R.; Elatharasan, G.
Frictions stir welding of dissimilar alloys are an efficient way in industrial applications. The effect of joining dissimilar alloys (AA6061-AA7075) has improves the mechanical strength of the welded joint. This work investigated the micro-hardness and mechanical properties of frictions stir welded dissimilar alloys. Aluminium alloy is heat treatable and may be subjected to either hot working or cold working. The heat treatment is followed by revolutionising and precipitation hardening. Microhardness was measured at various zones of the welded joints. The tensile properties of dissimilar joints are characterised. Tensile test results distributed the material flow and the stress-strain curve designates the mechanical strength of the frictions stir welding parameters. Cylindrical threaded profile has an important role among the other tool profiles. It contributes 93% to the overall efficiency. The high strength of 172 MPa was attained in the tool which is made up of cylindrical threaded pin profiled tool. This work inferred that the rotational speed, transverse speed, and D/d ratio for cylindrical threaded are considered more efficient. Maximum tensile strength could be obtained from the cylindrical threaded tool and it is comparatively high than other materials. Tensile and hardness measurement were done on this part of material characterisation.